Ultrasound Guidance in Performing a Tendoscopic Surgery to Treat Posterior Tibial Tendinitis: A Useful Tool? - Akinobu Nishimura; Shigeto Nakazora; Aki Fukuda; Ko Kato; Akihiro Sudo (Case Reports in Orthopedics)
A 25-year-old man with a pronation-external rotation type of fracture was surgically treated using a fibular plate. Five years later, he underwent resection of bone hyperplasia because of the ankle pain and limitation of range of motion. Thereafter, the left ankle became intermittently painful, which persisted for about one year. He presented at the age of 43 with persistent ankle pain. Physical and image analysis findings indicated a diagnosis of posttraumatic posterior tibial tendinitis, which we surgically treated using tendoscopy. Endoscopic findings showed tenosynovitis and fibrillation on the tendon surface. We cleaned and removed the synovium surrounding the tendon and deepened the posterior tibial tendon groove to allow sufficient space for the posterior tibial tendon. Full weight-bearing ambulation was permitted one day after surgery and he returned to his occupation in the construction industry six weeks after surgery. The medial aspect of the ankle was free of pain and symptoms at a review two years after surgery. Although tendoscopic surgery for stage 1 posterior tibial tendon dysfunction has been reported, tendoscopic surgery to treat posttraumatic posterior tibial tendinitis has not. Our experience with this patient showed that tendoscopic surgery is useful not only for stage 1 posterior tibial dysfunction, but also for posttraumatic posterior tibial tendinitis.